Geometric vs. algebraic approach: A study of double imaginary characteristic roots in time-delay systems. Issue 1 (July 2017) - Irofti, Dina; Boussaada, Islam; Niculescu, Silviu-Iulian
Abstract: This paper studies double imaginary characteristic roots in the case of time-delay systems with two delays as parameters. We aim to identify the direction in which double roots cross the imaginary axis, when the delay parameters change. To determine what happens when parameters are under a small perturbation, we present two methods: the algebraic and geometric approaches. Taking a theoretical example, we show that, even if the two methods are conceptually different, the provided results are consistent.